1972
DOI: 10.1037/h0082285
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Identification in Canada: A cross-cultural investigation.

Abstract: A multidimensional scaling analysis of paired comparisons ratings was applied to the problem of ethnic identity in Canada. French-and English-Canadian first year high school students rated the similarity between several pairs of stimuli which included, among others, the labels MYSELF, FRENCH CANADIAN, ENGLISH CANADIAN, CANADA, etc. The findings revealed a strong regional affiliation on the part of both cultural groups; however, the English-Canadian children evidenced strong national affiliations as well. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

1979
1979
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…These initial studies have been conducted in Canada (Taylor et al 1972;Taylor et al 1973), Wales (Giles et al 1977;Christian et al 1976) and in French speaking areas of the United States ), contexts where language differences form the fundamental basis of social categorization. Language emerged in these contexts as particularly important, with the exception of Franco-Americans who have no facility in the French language.…”
mentioning
confidence: 99%
“…These initial studies have been conducted in Canada (Taylor et al 1972;Taylor et al 1973), Wales (Giles et al 1977;Christian et al 1976) and in French speaking areas of the United States ), contexts where language differences form the fundamental basis of social categorization. Language emerged in these contexts as particularly important, with the exception of Franco-Americans who have no facility in the French language.…”
mentioning
confidence: 99%
“…Taylor's investigations of ethnic identity in Canada (e.g. Taylor, Bassilli & Aboud, 1973, Taylor, Simard & Aboud, 1972 in which the salience of language as a dimension of ethnic identity was demonstrated, also stimulated social psychologists to take language more seriously. Another important stimulus was Giles and Bourhis' (Bourhis, 1979;Giles, Bourhis & Taylor, 1977) incorporation of Tafjel's (1974,1978, see also 1982) theory of intergroup relations into their formulations.…”
Section: Language and Social Identitymentioning
confidence: 95%
“…Past research has shown that people in different cultures have different perceptions of the scale descriptors and the traits measured by a questionnaire (Forgas et al 1977;Hermann and Raybeck 1981;Rudmin 1994;Taylor et al 1972;Tzeng and Everett 1985;Tzeng et al 1976;Waston et al 1998). To assure cross-cultural adaptation of the WHOQOL questionnaire, the WHOQOL Group has published many guidelines (World Health Organization 1992, 1993, 1995a-d, 1996.…”
Section: The Significance Of Subculturesmentioning
confidence: 97%